MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS Wizer.me MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS - Ramadhani Ramadhani; Shuaibatul Aslamiah Ritonga (Universitas Asahan, 2022)
The destination and goal of this research is whether the Wizer.me-based blended learning model can successfully improve mathematical literacy skills. The design of this article is the pretest and posttest control groups. The article used by the researcher is a quasi-experimental type. The instrument applied is an essay test and the process of taking part of the members is random. All members of the school used are class VII SMP Negeri 23 Medan which has 6 classes. Some of the members or samples studied were from students in room VII-A totaling 25 people and room VII-B totaling 25 people. To analyze the data by calculating the mean, normality of the data, homogeneity the data, hypotesis testing and analysis of the student's answer process. From the results obtained that all data analysis of students in class VII-A who were given treatment was higher than students in class VII-B who were not treated, namely 9.2 > 5.8. The conclusion is that the Wizer.me-based blended learning model improves students' mathematical literacy skills.